Potential role and therapeutic implications of glutathione peroxidase 4 in the treatment of Alzheimer’s disease - Yanxin Shen; Guimei Zhang; Chunxiao Wei; Panpan Zhao; Yongchun Wang; Mingxi Li; Li Sun (Neural Regeneration Research, 2025)
Alzheimer’s disease is an age-related neurodegenerative disorder with a complex and incompletely understood pathogenesis. Despite extensive research, a cure for Alzheimer’s disease has not yet been found. Oxidative stress mediates excessive oxidative responses, and its involvement in Alzheimer’s disease pathogenesis as a primary or secondary pathological event is widely accepted. As a member of the selenium-containing antioxidant enzyme family, glutathione peroxidase 4 reduces esterified phospholipid hydroperoxides to maintain cellular redox homeostasis. With the discovery of ferroptosis, the central role of glutathione peroxidase 4 in anti-lipid peroxidation in several diseases, including Alzheimer’s disease, has received widespread attention. Increasing evidence suggests that glutathione peroxidase 4 expression is inhibited in the Alzheimer’s disease brain, resulting in oxidative stress, inflammation, ferroptosis, and apoptosis, which are closely associated with pathological damage in Alzheimer’s disease. Several therapeutic approaches, such as small molecule drugs, natural plant products, and non-pharmacological treatments, ameliorate pathological damage and cognitive function in Alzheimer’s disease by promoting glutathione peroxidase 4 expression and enhancing glutathione peroxidase 4 activity. Therefore, glutathione peroxidase 4 upregulation may be a promising strategy for the treatment of Alzheimer’s disease. This review provides an overview of the gene structure, biological functions, and regulatory mechanisms of glutathione peroxidase 4, a discussion on the important role of glutathione peroxidase 4 in pathological events closely related to Alzheimer’s disease, and a summary of the advances in small-molecule drugs, natural plant products, and non-pharmacological therapies targeting glutathione peroxidase 4 for the treatment of Alzheimer’s disease. Most prior studies on this subject used animal models, and relevant clinical studies are lacking. Future clinical trials are required to validate the therapeutic effects of strategies targeting glutathione peroxidase 4 in the treatment of Alzheimer’s disease.